A novel panel of α-synuclein antibodies reveal distinctive staining profiles in synucleinopathies. - Jess-Karan S Dhillon; Cara Riffe; Brenda D Moore; Yong Ran; Paramita Chakrabarty; Todd E Golde; Benoit I Giasson (PLoS ONE)
Synucleinopathies are a spectrum of neurodegenerative diseases characterized by the intracellular deposition of the protein α-synuclein leading to multiple outcomes, including dementia and Parkinsonism. Recent findings support the notion that across the spectrum of synucleinopathies there exist diverse but specific biochemical modifications and/or structural conformations of α-synuclein, which would give rise to protein strain specific prion-like intercellular transmission, a proposed model that could explain synucleinopathies disease progression. Herein, we characterized a panel of antibodies with epitopes within both the C- and N- termini of α-synuclein. A comprehensive analysis of human pathological tissue and mouse models of synucleinopathy with these antibodies support the notion that α-synuclein exists in distinct modified forms and/or structural variants. Furthermore, these well-characterized and specific tools allow the investigation of biochemical changes associated with α-synuclein inclusion formation. We have identified several antibodies of interest with diverse staining and epitope properties that will prove useful in future investigations of strain specific disease progression and the development of targeted immunotherapeutic approaches to synucleinopathies.